Decreased C3 Activation by the devR Gene-Disrupted Mycobacterium tuberculosis Strain in Comparison to the Wild-Type Strain. (18th May 2013) - Narayan Rao, V.; Manivannan, S.; Tyagi, J. S.; Ramanathan, V. D.
Abstract : Activation of the complement component C3 is an important step in the complement cascade, contributing to inflammatory mechanisms. Considerable research on gene-disrupted mycobacterial strains using animal models of tuberculosis infection has reported the roles of some of the mycobacterial genes during tuberculosis infection. The aim of the present study was to assess the pattern of complement activation by the devR gene-disrupted Mycobacterium tuberculosis H37Rv strain and compare with that by its wild-type strain. In vitro complement activation at the level of C3 by the gene-disrupted strain, its complemented strain, and wild-type strain was performed using solid-phase ELISA. It was observed that the ability of devR gene-disrupted M. tuberculosis H37Rv to activate C3 was significantly reduced in comparison to its wild-type strain (P < 0.05 ). In addition, C3 activation by the complemented devR mutant strain was almost similar to that of the wild strain, which indicated that the reduced ability to activate C3 could potentially be due to the deletion of devR gene. These findings indicate that the gene devR probably aids in complement activation and contributes to the inflammatory processes during tuberculosis infection.